Lição de Coisas no século XIX e seus rebatimentos para uma educação aberta aos saberes dos educandos - Silva, Edna Maria Lopes da (2015)
This Thesis performs a search about the Intuitive Teaching method used in Brazil at the end of the nineteenth century, and on its proposal in seeking the reversal of the inefficiency of school education offered to the popular classes. In order to deepen the discussion, we chose the Didactic Manual by Norman Allison Calkins, First Lessons of Things, based on the educational initiatives of Henri Pestalozzi. The choice of the Manual was formed from the Thesis argument, that it was a unique and innovative proposal, which involved not only a method, but a pedagogical theory that waved as the possibility of opposition to the dominant society, until then, had as a means of access to knowledge. Using a dynamic open to knowledge and to the student's emotions, without neglecting the intellectual knowledge, the philosophical theory of the method presents a way of overcoming the educational tradition, very attached to traditional teaching, which did not seek to open ways to the student's knowledge, dialogue, and reflection. In argumentative detachment of Thesis, was being imposed a way that prioritized deepened the educational conceptions of Renaissance humanism and other, present in the theoretical ideas that direct their criticism of the teaching bookish , abstract and pedantic, such as Rabelais (1493-1553), Montaigne ( 1553 -1592 ), taken over by Comenius ( 1592-1670 ) and Rousseau ( 1712-1778 ). In the investigative process, there was the relationship of the fundamentals of intuitive method contained in the Calkins‟ proposed with the principles of Popular Education, under Freire's perspective, taking care to evidence approaches and detachment. As a result, it is concluded that in both proposals are present critical to the model of access to systematic knowledge dominant; both prioritize the encouragement of the student's curiosity and "things" of their world. The educator's role, as such proposals, is the proponent of educating the adventure of learning and cultivating their sensitivity. The intuitive method presents an accessible and necessary proposal to the educator, especially in popular education practices, because it provides the learner to improve its perception of skills and action‟s qualification. This feature helps you to see, hear, feel and intuit more and better about and from their world, since its opening to dialogue and reflection enables an intellectualized education, so necessary nowadays.